Can Energy Trading be a Solution for Indonesia’s Energy Mix Goal through Solar Energy? - Berian, Zagy Y.; Kaulika, Vincent O. (Purnomo Yusgiantoro Center, 2020)
Climate change has gotten more and more serious worldwide. To secure the future for our next generation, we need to change the way we use and consume energy from a cleaner source. In Indonesia, this effort is shown through Presidential Regulation No. 22/2017, or general planning of national energy (RUEN) indicates that Indonesia’s government is targeting 23% of energy mix via solar power. However, today, through various industries and consumers level adoption, it is still hard to achieve. The consumer study by Institute for Essential Services Reform (IESR) found that the main issues for the adoption in Jabodetabek are due to lack of consumer incentive, lack of clear benefits of electricity reduction, and poor education about how to install solar power on the consumer level. Throughout this paper, the authors are going to propose a way for energy trading to solve such issues from a top-down perspective. It will start from how the current condition at the consumer level is, the potential scenario, stakeholder benefits analysis, potential location case study, to the commercialization through economic analysis. To achieve the goal of incentivizing customer yet still creating economic sense for the potential investors, which we use state-owned electricity company (PLN) as an example to provide alternatives to a larger scale power plant investment, we experiment on multiple profit sharing mechanisms and scenarios. By varying the profit-sharing factor, we get that 35%-65% profit sharing mechanism gives PLN an acceptable payback period and decent profit margin while can still incentivize the customer. From this study on, we can further study the customer buy-in (incentive level) elasticity in correlation with the variation of profit share that is still profitable for the investor or PLN before deciding on the policy.